A study on the factors influencing the adoption of mobile payment system in Nigeria - Hamza, Aminu (Kulliyyah of Information & Communication Technology, International Islamic University Malaysia, 2014)
The proliferation of handheld devices and the high-speed mobile network have created another revolution in the world of commerce. Despite the continuous emerging payment solutions and abundant facilitating technologies, the level of mobile payment system adoption is quite low. Researchers focused their attention mainly on mobile payment business model and mobile payment software/infrastructures architectures with relatively little attention paid to the factors influencing the adoption. Moreover, researchers paid very little attention on issues regarding mobile payment system adoption in developing countries. Accordingly, this study examined the factors that determine the adoption of mobile payment system and how their influence differs by gender of the students of tertiary institutions in Nigeria. Technology Acceptance Model (TAM) was used with three additional variables to form the conceptual model. The study was conducted in three Universities in Kano state, Nigeria. Purposive sampling method was used with a total valid 214 respondents which involved the students of Bayero University Kano (BUK), North-West University, and Kano University of Science and Technology (KUST) Wudil, Kano, Nigeria. The results of the multiple regression analysis revealed that perceived ease of use (PEOU), perceived usefulness (PU), perceived compatibility (PC) and social norm (SN) have significant and positive correlation with the behavioural intention to adopt mobile payment system. The findings from the independent t-test also revealed that there is a significant difference on the influence of PEOU and SN among the gender of the students with male having high perceived ease use (PEOU) over female counterpart, while social norm (SN) influences female more than their male counterpart in adopting mobile payment. The study provided empirical support of the background theory outside the context of developed countries and contributed significantly to the existing literature in the field of mobile payment. Secondly, the study provided input about the critical success factors of the adoption of mobile payment system among mobile users. Thirdly, the study will help authorities to make relevant adjustments regarding the cashless-policy to make it more effective in the economy.